Numerical Study for HAWT Wake shape with different Angles of Attack (Journal of Engineering, 2021)
Increasing world demand for renewable energy resources as wind energy was one of the goals behind research optimization of energy production from wind farms. Wake is one of the important phenomena in this field. This paper focuses on understanding the effect of angle of attack (α) on wake characteristics behind single horizontal axis wind turbines (HAWT). This was done by design three rotors different from each other in value of α used in the rotor design process. Values of α were (4.8˚,9.5˚,19˚). The numerical simulations were conducted using Ansys Workbench 19- Fluent code; the used turbulence model was (k-ω SST). The results showed that best value for extracted wind energy was at α=19˚, spread distance of wake behind single HAWT was inversely proportional with α value. Highest turbulence intensity level was in small values of α =4.8֯ and 9.5֯, which explain presence of meandering phenomenon in these two cases on contrast of α=19֯, while symmetry in wake shape was more obvious in α=19֯ than other cases due to the moderate turbulence intensity which was found in this case, which indicates that lowest aerodynamics loads on rotor components was in α=19˚. So best distribution for turbines in farm could be achieved at use high values of α in comparison to low values.